2021
DOI: 10.2463/mrms.mp.2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Image Quality and Utility of Synthetic MRI in the Breast

Abstract: Purpose: Synthetic MRI reconstructs multiple sequences in a single acquisition. In the present study, we aimed to compare the image quality and utility of synthetic MRI with that of conventional MRI in the breast. Methods:We retrospectively collected the imaging data of 37 women (mean age: 55.1 years; range: 20-78 years) who had undergone both synthetic and conventional MRI of T2-weighted, T1-weighted, and fatsuppressed (FS)-T2-weighted images. Two independent breast radiologists evaluated the overall image qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, MAGiC has limitations. Compared with conventional FLAIR images, synthetic FLAIR images have inferior image quality (lower contrast-to-noise ratio) ( West et al, 2017 ; Fujioka et al, 2021 ). Furthermore, due to partial volume effects, the interface between the brain parenchyma and cerebrospinal fluid (CSF) is hyperintense on a synthetic FLAIR image; therefore, a conventional FLAIR image needs to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, MAGiC has limitations. Compared with conventional FLAIR images, synthetic FLAIR images have inferior image quality (lower contrast-to-noise ratio) ( West et al, 2017 ; Fujioka et al, 2021 ). Furthermore, due to partial volume effects, the interface between the brain parenchyma and cerebrospinal fluid (CSF) is hyperintense on a synthetic FLAIR image; therefore, a conventional FLAIR image needs to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…It holds potential for synthesizing contrast-enhanced images from unenhanced ones. This is beneficial for contrast-sensitive patients like those with allergies, asthma or pregnancy and for those with discomfort in long MRI sessions (42).…”
Section: Synthetic Mrimentioning
confidence: 99%
“…The recently proposed synthetic MRI (syMRI) [ 18 20 ] uses a multiple-dynamic multiple-echo (MDME) acquisition method for simultaneous measurement of quantitative values including T1 and T2 relaxation time and proton-density (PD) mapping in one single scan, with the advantage of shorter scan time and independence of MRI scanners and parameters [ 21 , 22 ]. Several studies have confirmed the clinical utility of syMRI in malignancy identification [ 23 ], molecular typing [ 24 ], and therapeutic response assessment [ 25 , 26 ] in various cancers.…”
Section: Introductionmentioning
confidence: 99%